2018
DOI: 10.21037/jss.2018.05.26
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism increases 90-day postoperative complications in patients undergoing primary single level anterior cervical disectomy and fusion: a matched control analysis

Abstract: Hypothyroidism is a risk factor for worse postoperative outcomes in patients undergoing primary ACDF. Appropriate preoperative optimization with thyroid hormone supplementation could potentially minimize the incidence of developing numerous medical complications, in addition to potentially lowering readmission rates and the total cost of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…PearlDiver is a commercially available database that is Health Information Portability and Affordability Act compliant and has been used extensively for orthopaedic-related research. [8][9][10] Since the database contains de-identified patient information, the study was exempt from our institution's internal review board approval. Patients were queried using the International Classification of Disease, Ninth Revision (ICD-9) and Current Procedural Terminology (CPT) codes.…”
Section: Methods Databasementioning
confidence: 99%
“…PearlDiver is a commercially available database that is Health Information Portability and Affordability Act compliant and has been used extensively for orthopaedic-related research. [8][9][10] Since the database contains de-identified patient information, the study was exempt from our institution's internal review board approval. Patients were queried using the International Classification of Disease, Ninth Revision (ICD-9) and Current Procedural Terminology (CPT) codes.…”
Section: Methods Databasementioning
confidence: 99%
“…In 2018, Vakharia et al published the first study evaluating complications directly associated with hypothyroidism in the first 90 days post-single level anterior cervical discectomy and fusion (ACDF). They found that hypothyroid patients had higher rates of non-healing wounds (OR 2.27, 95% CI: 1.11-4.62, p < 0.0232), PE (OR 2.16, 95% CI: 1.51-3.09, p < 0.001), MI (OR 2.10, 95% CI: 1.43-3.08, p < 0.001), and 90-day readmission (OR 1.45, 95% CI: 1.41-1.49, p < 0.001) [ 17 ]. Although our study also showed increased rates of wound complications in cervical fusions, we elected to include all types of cervical fusions, both posterior and anterior, in an effort to eliminate the selection bias that limited their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As has been demonstrated in other orthopedic Medicare database research, CCI is a marker to ensure that both cohorts were matched properly and no statistical difference existed between the 2 groups. 12,13 Since comorbidities represent categorical variables, a Pearson chi-square analysis was performed to determine the significance between the study and control groups, whereas Welch's t test was utilized to test for significance in CCI between the cohorts.…”
Section: Discussionmentioning
confidence: 99%